Voltage-driven displacement of magnetic vortex cores. (3rd August 2020) - Ghidini, M; Pellicelli, R; Mansell, R; Pesquera, D; Nair, B; Moya, X; Farokhipoor, S; Maccherozzi, F; Barnes, C H W; Cowburn, R P; Dhesi, S S; Mathur, N D
Abstract: Magnetic vortex cores in polycrystalline Ni discs underwent non-volatile displacements due to voltage-driven ferroelectric domain switching in single-crystal BaTiO3 . This behaviour was observed using photoemission electron microscopy to image both the ferromagnetism and ferroelectricity, while varying in-plane sample orientation. The resulting vector maps of disc magnetization match well with micromagnetic simulations, which show that the vortex core is translated by the transit of a ferroelectric domain wall, and thus the inhomogeneous strain with which it is associated. The non-volatility is attributed to pinning inside the discs. Voltage-driven displacement of magnetic vortex cores is novel, and opens the way for studying voltage-driven vortex dynamics.